Lymphocytic Esophagitis in Nonachalasia Primary Esophageal Motility Disorders: Improved Criteria, Prevalence, Strength of Association, and Natural History. (December 2016) - Putra, Juan; Muller, Kristen E.; Hussain, Zilla H.; Parker, Siddhartha; Gabbard, Scott; Brickley, Elizabeth B.; Lacy, Brian E.; Rothstein, Richard; Lisovsky, Mikhail
Abstract : Lymphocytic esophagitis (LE) is a histologic pattern with no established clinical correlates in the majority of patients. The goal of this study was to evaluate the association between nonachalasia primary esophageal motility disorders (PEMD) and LE. Sixty-nine patients with PEMD and esophageal biopsies, including 22 with nutcracker esophagus, 33 with ineffective motility, and 14 with diffuse spasm, constituted the study group. The control group consisted of 70 patients with severe dysmotility-negative gastroesophageal reflux disease requiring referral for Nissen fundoplication. To improve the criteria for LE, a lymphocyte reference range at different esophageal levels was first established in 17 healthy volunteers. The cutoffs for normal intraepithelial lymphocytes, defined as lymphocyte levels not exceeding mean level±2 SDs, were set at 62, 46, and 41 lymphocytes per high-power field at 0 to 2, 5, and 10 cm above the gastroesophageal junction, respectively. Predominantly focal peripapillary LE was observed in approximately 40% of patients with nutcracker esophagus or diffuse spasm and in 20% of patients with ineffective motility, in comparison with 4% of patients with dysmotility-negative gastroesophageal reflux disease ( P <0.035 vs. any subtype of PEMD). Overall, LE was strongly associated with PEMD in multivariate analysis (adjusted odds ratio, 7.93; 95% confidence interval, 2.26-27.9; P =0.001). LE had a chronic course in 56% of the patients with follow-up biopsies. In conclusion, LE has a strong association with PEMD, suggesting the utility of LE in raising the possibility of PEMD.